2003
DOI: 10.1002/jssc.200301578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surfactant‐assisted pressurized hot water extraction for marker compounds in Radix Codonopsis pilosula using liquid chromatography and liquid chromatography/electrospray ionization mass spectrometry

Abstract: Evaluation of surfactant-assisted pressurized hot water extraction for marker compounds in Radix Codonopsis pilosula using liquid chromatography and liquid chromatography/electrospray ionization mass spectrometryIn the move towards the elimination of organic solvents in the extraction process in botanicals, a new method combining surfactant and pressurized hot water extraction (PWHE) with an applied temperature below the boiling point and lower pressure from 10 to 20 bar was developed for the analysis of marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…It has been observed that extracts with varying active components or marker compounds are obtained when using different methods of extraction. 15,17,18 This will in turn affect the bioactivity and toxicity of the botanical extracts obtained. Hence, the method of extraction used needs to be validated to ensure that it has the required method precision and extraction efficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that extracts with varying active components or marker compounds are obtained when using different methods of extraction. 15,17,18 This will in turn affect the bioactivity and toxicity of the botanical extracts obtained. Hence, the method of extraction used needs to be validated to ensure that it has the required method precision and extraction efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…The method used for solid sample preparation was found to have good method precision and also comparable or higher extraction efficiencies with reference to Soxhlet extraction and sonication, for medicinal plants such as Scutellariae radix, radix glycyrrhizae/liquorice and others. 15,17,18 The amount of extract obtained from the medicinal plant was found to be 112.5 AE 12.6 mg (n ¼ 4), and the baicalein content was determined by HPLC to be 14.26 AE 0.48 mg/g (n ¼ 5). Hence, the plant extracts used were 2.2, 1.12 and 0.45 mg/mL for the high-, mid-and low-dose groups, respectively.…”
Section: Preparation Of Plant Extracts and Animal Studiesmentioning
confidence: 99%
“…For components, such as tanshinone I and IIA in S. miltiorrhiza, PLE using methanol was found to give comparable or higher extraction efficiencies compared to PHWE with reference to Soxhlet extraction [46]. For the analysis of marker compounds in R. codonopsis pilosula (DangShen), it was observed that PHWE give lower extraction efficiencies compared to Soxhlet extraction [45]. To improve the extraction efficiencies of methods using PHWE, surfactants, such as Triton X-100 and sodium dodecyl sulfate (SDS) may be added into the water to enhance the solubility of target compounds present in the botanicals.…”
Section: Preparation Of Samplementioning
confidence: 89%
“…A novel MAE method had been developed for the extraction and determination of tanshinones (tanshinone IIA, cryptotanshinone and tanshinone I) from the root of Salvia miltiorrhiza with analysis by HPLC [28,29]. Other methods, such as the use of SFE that used carbon dioxide and some form of modifiers had been used [45,48] in the extraction of compounds present in medicinal plants [25,26,30,31].…”
Section: Preparation Of Samplementioning
confidence: 99%
See 1 more Smart Citation